2006
DOI: 10.17487/rfc4593
|View full text |Cite
|
Sign up to set email alerts
|

Generic Threats to Routing Protocols

Abstract: This memo provides information for the Internet community. It does not specify an Internet standard of any kind. Distribution of this memo is unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 4 publications
0
55
0
Order By: Relevance
“…Because this document introduces an extended community that will generally be used to affect route selection, the analysis in Section 4.5 ("Falsification") of [RFC4593] is relevant. These issues are neither new nor unique to the origin validation extended community.…”
Section: Security Considerationsmentioning
confidence: 99%
“…Because this document introduces an extended community that will generally be used to affect route selection, the analysis in Section 4.5 ("Falsification") of [RFC4593] is relevant. These issues are neither new nor unique to the origin validation extended community.…”
Section: Security Considerationsmentioning
confidence: 99%
“…This section sets the stage for the development of the analysis by applying the systematic approach proposed in [Myagmar2005] to the routing security, while also drawing references from other reviews and assessments found in the literature, particularly [RFC4593] and [Karlof2003] (i.e., selective forwarding, wormhole, and sinkhole attacks). The subsequent subsections begin with a focus on the elements of a generic routing process that is used to establish routing assets and points of access to the routing functionality.…”
Section: Considerations On Rpl Securitymentioning
confidence: 99%
“…The assessment in Section 4.2 indicates that there are attacks against the confidentiality of routing information at all points of access. This threat may result in disclosure, as described in Section 3.1.2 of [RFC4593], and may involve a disclosure of routing information.…”
Section: Dummy Nodementioning
confidence: 99%
See 1 more Smart Citation
“…Security Considerations Security issues are described in Section 5.4. The security considerations in RFC 4919 [RFC4919], RFC 4944 [RFC4944], and RFC 4593 [RFC4593] apply as well.…”
Section: Support Of Managementmentioning
confidence: 99%